Formation of Internet Culture of the future teacher of music art in the educational environment of Higher Education Institution - Dotsenko, S.; Zhou, An (New Collegium, 2022)
The issue of "Internet Culture" is considered and the stages of its formation are customary, professional, pedagogical, and ideological. Peculiarities and risks of its functioning in the modern educational environment are determined. The relationship between the Internet and culture is analysed. The conditions and possible directions for the formation of Internet culture of the future teacher of musical art are offered. Positive results of studying the discipline "Innovative pedagogy" are given. Conclusions and proposals on improving the system of training future teachers of music in the educational environment of the Free Economic Zone are substantiated. Two components of Internet culture are substantiated: communicative and operational-technological. The communicative component includes the ability to find the necessary reliable information, to master the means of communication, and knowledge of the ethics of network communication. The operational and technological component consists of the ability to master software products; the ability to work with search engines; the ability to use e-mail; knowledge of the rules of safe use of the Internet, etc. The problems of formation of Internet culture of the future teacher of musical art are outlined: 1) formation of the system of information concepts; 2) the teacher’s ability to carry out information activities; 3) readiness of the teacher for constant self-education in the field of Internet technologies and effective use of electronic resources and sources of information; 4) conscious regulation of their own behaviours in the network, moral and legal norms, compliance with network etiquette.